Towards valuing the revenues of the local tax system in Algeria with reference to the municipalities and the state of M’Sila during 2020-2023 - oualhi, Boualam (Journal of Research in Finance and Accounting, 2024)
This study aimed to address the proposed problem of how to value the revenues of the local tax system in Algeria by applying it to the municipalities and the state of M'Sila during the period 2020-2023 based on official statistics, in order to address in the same effort, the obstacles that still stand in the way of achieving the goals set for the local tax system. The study ultimately concluded by the need to adopt a set of practical proposals to improve the performance of this system in light of the new trend towards reforming local finance.